Wood-derived nanostructured hybrid for efficient flame retarding and electromagnetic shielding. (June 2021) - Chen, Junqing; Zhu, Zhaodong; Zhang, Hui; Tian, Shenglong; Fu, Shiyu
Graphical abstract: Highlights: A non-carbonized multifunctional nanostructured wood for electromagnetic shielding is fabricated. The material progress excellent flame retardancy and Photothermal conversion performance. The nanostructured wood shows good thermal stability and ultra-lightness, and is a sustainable material. Abstract: Delignified wood with 3D porous structure provides a good platform for constructing multifunctional electromagnetic shielding materials. The objective of this work is to fabricate a non-carbonized nanostructured wood composite by in-situ polymerization of aniline in H3 PO4 acidic medium for flame retardancy and electromagnetic shielding. The wood aerogel with hierarchical porous structure after removing lignin and hemicellulose is almost composed of cellulose and provided a satisfactory 3D network structure. The wood porous channels were coated with polyaniline (PANI) by in-situ polymerization providing a high conductivity (22.07 S/m). The polyaniline-wood aerogel (PANI-WA) with a thickness of 2–3 mm showed a good electromagnetic interference (EMI) shielding effectiveness of 27.63 dB in the X band (8.2–12.4 GHz). Notably, the material simultaneously possesses excellent flame retardancy, which can self-extinguish and retain its original shape after repeated ignition. PANI-WA also exhibits the ability of photothermal conversion under near-infrared (NIR) irradiation. The interesting PANI-WA has a good potential application for electromagnetic shielding materials with flame retardancy and photothermal conversion under NIR.